The maritime economy of ancient Cyprus in terms of the new institutional economics - Parpas, Andreas P. (Archaeopress Archaeology, 2022)
This study considers the maritime economy of ancient Cyprus from 1450 BC to 295 BC, combining, for the first time, three distinct disciplines, that is History, Archaeology and Economic theory. The principles of New Institutional Economics are used to trace the island's institutions and their continuity and to reconstruct its maritime history.